Implementation of Augmented Reality Technology for Basic First Aid Mobile Application - Khor, Yue Zhen; Wahid, Noorhaniza (Applied Information Technology And Computer Science, 2023)
Augmented Reality (AR) is widely applied in many fields including first aid training in foreign countries. However, Malaysian have relatively low awareness of first aid due to a lack of first-aid training and a difficult-to-understand static first-aid manual. These concerns prompted the creation of AR-First Aid, a first-aid-related mobile application. The AR technology implemented enables users to learn first aid kit items and skills in AR. AR-First Aid also includes a mock first aid exam and each state’s hospital list taken from the Ministry of Health’s website. Then, the Technology Acceptance Model (TAM) is utilized for the user acceptance testing of 30 secondary school students. The observation shows that only 4.3% of the respondents cannot access the AR features while the remaining 95.7% give positive feedback on the application. Hence, the main future improvement is to develop the application with the AR function that can be supported by more devices.